Validation of a Rubric to Evaluate Open Educational Resources for Learning - de la Rosa Gómez, Anabel (Behav Sci (Basel), 2019)
Open Educational Resources (OERs) include different web formats, such as audio, video, images and text that can be modified, redistributed and used for learning about a specific topic, however, it became pertinent to create an OER evaluation tool with content validity. The present work gives an account of the content validation process using a 41-criteria rubric, each one with three performance levels, developed from a documentary search on relevant aspects to be included in a learning object. Six expert judges were contacted and decided whether each criterion was essential, useful but not essential or not necessary. Based on this, the Content Validity Reason (CVR) was calculated, obtaining 32 validated criteria. Among some conclusions, it can be mentioned that the validation process of contents allowed the identification of those criteria that require modifications or, if necessary, can be discarded to increase the validity of the heading in its whole.